Analisis Dampak Kawasan Sentra Budidaya Lele Terpadu (KSBLT) Kabupaten Tuban di Kecamatan Merakurak Terhadap Usaha Budidaya Lele di Kecamatan Tuban - Kurniawan, Andi; Pramudia, Zulkisam; Amin, Abdul Aziz; Nurjannah, Nurjannah; Hidayat, Wahyu; Kurniati, Evi; Lusiana, Evellin Dewi; Ardian, Gatot; Amenan, M (Universitas Trunojoyo Madura, 2021)
As one of the efforts to increase production of catfish culture, the Government of Tuban Regency launched the establishment of The Integrated Catfish Cultivation Center Area (ICACA) in Merakurak Sub-District in 2018. The existence of ICACA makes the program to increase catfish aquaculture more coordinated and increase production of catfish cultivation in Tuban Regency. ICCCA not only has an impact on the aquaculture business in Merakurak District, but also in other sub-districts in Tuban Regency. However, studies that explore the impact of ICACA on aquaculture in other areas are rarely reported. This study analyzes the impact of the existence of ICACA on cultivation business in Tuban District in Tuban Regency. This study uses a descriptive method with a mixed method approach (qualitative and quantitative). The results of this study indicate the factors that are the impact of ICACA in Merakurak District on the development of catfish cultivation in Tuban District. Based on the analysis carried out in this study, the implementation of ICACA in Tuban Regency, especially related to the effect of ICACA on catfish cultivation in Tuban District, needs to be directed to the application of sustainable aquaculture based on the empowerment of local community groups.